LAW, RAPPING AND SOCIAL JUSTICE: RETHINKING TRUTH IN CONTEMPORANEITY - Mari Cristina de Freitas Fagundes; Ana Clara Correa Henning; Gabriela M. Kyrillos; Thais Luzia Colaço (European Scientific Journal, ESJ, 2014)
Our criminal justice system produces socially naturalized truths which authorize certain subjects’ discourse, and silence others’. Rapping, as a counterculture, produces resistance from peripheral spaces in the complex power and knowledge net around us. Rap lyrics problematize a form of violence present even inside the state action, either as classifying subjects or in it’s so-called democratic discourse. Those questions are reasoned in this paper, in bibliographic contribution and compositions analysis in this genre.